Faktor-Faktor yang Mempengaruhi Terjadinya Kekurangan Energi Kronik pada Ibu Hamil - Lilis Suryani; Merisa Riski; Rini Gustina Sari; Heru Listiono (Universitas Batanghari Jambi, 2021)
Chronic Energy Deficiency in pregnant women is a condition of the mother's lack of protein and energy intake during pregnancy which can cause health problems for the mother and the fetus. The purpose of this study was to determine the factors that influence the occurrence of chronic energy deficiency in pregnant women. This research is an analytical survey with a cross sectional research design, the study was conducted in June - August 2020 at the Pegayut Public Health Center, Pemulutan District, Ogan Ilir Regency, South Sumatra. The population in this study were all pregnant women who carried out ANC examinations at Pegayut Health Center in 2019 which totaled 369 people and the sample used in this study was the entire population of 369 people, data analysis used univariate (proportion), bivariate (chi square test) and multivariate (logistic regression) analysis. The analysis showed that maternal age at intervals of pregnancy (p value: 0,000) and parity (p vaue: 0,000) had a significant relationship with chronic energy deficiency, while the age of pregnant women (p value: 0.147) had no significant relationship with the occurrence of energy deficiency. chronicles. Based on the final model of multivariate analysis, the variable that has the greatest effect on chronic energy deficiency is the pregnancy interval variable. It is hoped that pregnant women should carry out routine pregnancy checks at least 4 times during pregnancy to monitor the health of the mother and baby so as to prevent complications of pregnancy and childbirth.